Iconografie urbane : metafore, paradigmi, tipologie. Presupposti epistemologici per un’estetica delle immagini - Wunenburger, Jean-Jacques (Scenari, 2021)
In which way can be defined the Imagology (science and practices of images) in the field of Urbanism? One can start from a recurring and metaphorical image of the city: the vitalist metaphor of the body, and therefore of the city-body. It has given the rise in history to a recurring primary metaphor, of the organicist type, then to a secondary version, distinguished by the image of the body-machine, at the moment in which the living organism has been considered as the equivalent of the artefact of the machine. These metaphor images can be used both in an antinomic and in a syncretic regime. In the field of Urbanism, these images are currently constructed and interpreted from two mythologies (themata, ideologies) of the city: one naturalist (from the Greek, phytological) and the other artificial (demiurgic). Each of these cognitive and interpretative paradigms informs, orients, the urban gaze and influences the production and use of images. Finally, one could integrate an indicator for reading images, allowing them to be classified according to their aesthetic depth and symbolic richness. In every narrative and iconic representation, different semantic stratifications of their content (imagerie, imaginary, imaginary) are mixed in variable proportions. This complexity of the image, source of ambivalence and hybridization, would make it possible to access a meta-discourse on urban images and to understand in what sense they participate in an “image of the city”. (K. Lynch) and how they are creators, innovators and inspire a new aesthetic design.